PENGARUH KETERSEDIAAN FASILITAS, KENYAMANAN DAN PELAYANAN TERHADAP MINAT MEMBACA DI PERPUSTAKAAN UMUM DAERAH KEFAMENENU KABUPATEN TIMOR TENGAH UTARA - Thein, Imelda (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This study aims to determine the effect of the availability of facilities, comfort and service to interest in reading in the Kefamenanu Regional Public Library. This research was conducted at the Kefamenanu Regional Public Library. The sample determination technique uses the Slovin formula with a sample of 100 people. Analysis Method The data used are validity and reliability analysis, classic assumption test and multiple linear regression using SPSS 21 program. The results showed that based on the partial test (t test), the availability of facilities, convenience and services had an effect on reading interest in the City Public Library Kefamenanu. Simultaneously (F test), Availability of Facilities, Convenience and Services has an effect on Reading Interest with a significance of 0,000 <0,05.